Theories of globalization - Axford, Barrie (Cambridge, UK : Polity, 2013)
'Theories of Globalization' offers students and scholars a comprehensive and critical introduction to the concept of globalization. Barrie Axford expertly guides readers through the full range of perspectives on the topic, from international political economy to geography, global anthropology to cultural and communication studies.
Includes bibliographical references (pages 191-222) and index.
Keywords: Globalization